A SYSTEMATIC REVIEW OF TAX POLICY DURING CRISES: CURE OR CURSE? - Syaifudin, Achmad Ali; Prastyono, Anggi; Rahman, Rheza Auliya (Natapraja, 2024)
This study examines prior research findings on the role of tax policy in economic stability, particularly in the contexts of crisis. Economic crises often spark debates about the effectiveness of tax policies—whether they serve as tools for recovery or exacerbate crisis conditions. Focusing on evaluating the impact of both expansionary and contractionary tax policies on economic stability during crises, this study employs a Systematic Literature Review (SLR) with the PRISMA approach to ensure replicability and transparency. Literature searches were conducted via the Scopus database, with inclusion criteria covering 20 studies published between 2019 and 2024. The selection process involved identifying, screening, and assessing relevant studies, emphasizing tax policies during economic crises. The findings reveal that tax policies have dual effects. On one hand, tax cuts and fiscal incentives can stimulate recovery by boosting consumption and investment. Conversely, ill-timed or poorly targeted tax hikes may deepen recessions by reducing liquidity and suppressing growth. The discussion highlights the need for responsive policy design tailored to economic conditions and coordinated with monetary measures. In line with public policy theory, particularly contingency theory, this study emphasizes that the effectiveness of tax policy is highly context-dependent and there is no one-size-fits-all solution.